EFEK MODERASI LITERASI GIDITAL PADA PENGARUH DIGITAL EKONOMI TERHADAP PERKEMBANGAN UMKM KOTA MEDAN - Tarigan, Imanuel; Siagian, Tomy Sun; Ningrum, Dhea Agusty; Rasyid, Mhd. Andi (Jurnal Manajemen dan Bisnis, 2024)
The development and economic growth of Indonesia is assisted by small and medium-sized micro enterprises (UMKM). With digital literacy as a moderator variable, this study aims to test the impact of the digital economy on UMKM's revenue in Medan City. In this study, a descriptive quantitative method was used; the sample used was a UMKM perpetrator in Medan City, with 100 respondents. Smart PLS version 3.0 is the analytical tool used. The results of this study show that the digital economy has a positive and significant impact on the income of small and medium-sized enterprises (SMEs) in the field. Digital literacy also plays an important role in regulating both variables. So, if digital literacy is maximized, UMKM's revenue will increase.